The Adaptation of Islamic Principles in Sarawak Traditional Malay House - Adibah, Yusuf; Khairul Aidil Azlin, Abdul Rahman; Azmal, Sabil; Nangkula, Utaberta; Nadzirah, Yusuf (Architecture Department, Faculty of Science and Technology, Universitas Islam Negeri (UIN) Maulana Malik Ibrahim Malang, Indonesia, 2021)
Historically, in the event of Islam's arrival in the Malay Archipelago, the ways of Islam were adapted to the lifestyle of the Malay community. It's part of modernizing traditional Malay thoughts (akliah) which is influenced by Islamic values and teachings. One of the manifestations of Islamic influence in the traditional Malay lifestyle can be identified from the design and characteristics of Traditional Malay houses, developed with underlying principles of Islam. This paper discusses the application of Islamic principles in Sarawak traditional Malay houses. The research was conducted on three traditional Malay houses chosen from Sarawak and located in Kuching, Sarawak. The methods of observation and case study were employed, focusing on the interior space of the house and certain other design components. In addition, interviews were performed with the owners of the three houses that comprised the samples and focus group discussions with 12 Malay people over 65. The findings indicate that three concepts may be related to Islam's characteristics in Sarawak: the concept of occupant social connections, residential space, and construction and design.